2016
DOI: 10.1038/srep32697
|View full text |Cite
|
Sign up to set email alerts
|

On the interplay between neoclassical tearing modes and nonlocal transport in toroidal plasmas

Abstract: This Letter presents the first observation on the interplay between nonlocal transport and neoclassical tearing modes (NTMs) during transient nonlocal heat transport events in the HL-2A tokamak. The nonlocality is triggered by edge cooling and large-scale, inward propagating avalanches. These lead to a locally enhanced pressure gradient at the q = 3/2 (or 2/1) rational surface and hence the onset of the NTM in relatively low β plasmas (β N < 1). The NTM, in return, regulates the nonlocal transport by truncatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…These effects have been extensively documented in many tokamaks and helical devices, namely in TEXT [4][5][6], TFTR [7,8], Tore Supra [9,10], RTP [11][12][13], ASDEX-U [14], JET [15], LHD [1,[16][17][18][19][20][21][22][23], HL-2A [24][25][26][27][28], Alcator C-Mod [29,30] and, more recently, in KSTAR [31]. Despite the reproducibility of these phenomena in very different plasma conditions, the underlying mechanism of the core response is still unclear.…”
Section: On the Correlation Between 'Non-local' Effects And Intrinsic...mentioning
confidence: 99%
“…These effects have been extensively documented in many tokamaks and helical devices, namely in TEXT [4][5][6], TFTR [7,8], Tore Supra [9,10], RTP [11][12][13], ASDEX-U [14], JET [15], LHD [1,[16][17][18][19][20][21][22][23], HL-2A [24][25][26][27][28], Alcator C-Mod [29,30] and, more recently, in KSTAR [31]. Despite the reproducibility of these phenomena in very different plasma conditions, the underlying mechanism of the core response is still unclear.…”
Section: On the Correlation Between 'Non-local' Effects And Intrinsic...mentioning
confidence: 99%
“…It can be observed that the Hurst parameters, self-similarity in turbulence, and large-scale radial correlation are all enhanced with the growing inward propagation of turbulent activities. In the transient NLT event, the interaction between the nonlocal transport and the neoclassical tearing mode (NTM) was observed (Ji et al 2016). A typical experiment for the interaction study is shown in Fig.…”
Section: Heat Transportmentioning
confidence: 99%
“…Fig. 29 Typical discharge waveforms with an onset of a 3/2 NTM during the nonlocal transport induced by SMBI (vertical yellow bar) in ECRHheated plasma at HL-2A(Ji et al 2016) …”
mentioning
confidence: 99%
“…离子驱动的阿尔芬级联模(ACs) [32] , 见图24 [33,34] . [36] . 此外, 也观察到了由电子鱼骨模触发的非局 域热输运过程, 研究结果表明磁扰动、长程相关、介 观尺度结构以及剪切流对非局域输运起到重要作 用 [37] .…”
Section: 在Hl-2a的反剪切位形放电中 成功观测到了快unclassified